Múltiple access protocols with Smart antenas in multilop ad Hoc Rural - area Networks - Sánchez G, Marvin; Tutor (Managua UNI, 2002)
Multihop ad hoc networking is a very appealing technology for the deployment of Wíreles data Networks. It eliminates the need for network planning and the reliance on fixed infrastructure, multihop add hoc networks are designed with a self - configuring capability and are able to adapt to the addition or removal of network radio units (nodes). This capability make then simple to install allowing unskilled users to quickly setup the network.
Tesis (Licenciate of Technology)- UNI, 2002.
Keywords: COMUNICACIONES TELECOMUNICACIONES; PROTOCOLO